2007
DOI: 10.1007/s12055-007-0024-7
|View full text |Cite
|
Sign up to set email alerts
|

One stage surgical treatment of renal cell carcinoma with extension upto right atrium — A case report

Abstract: Long term survival has been reported after complete resection of renal cell carcinoma with intravascular extension through renal vein into inferior vena cava (IVC) and right atrium(RA). We present the case of a 74-year-old man who underwent one stage surgical treatment for renal cell carcinoma with extension reaching up to IVC-RA junction with the support of cardiopulmonary bypass. (Ind J Thorac Cardiovasc Surg, 2007; 23: 153-155)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Noguchi K et al 5 reported the use of CPB in combination with hypothermic circulatory arrest (HCA) for complete tumor-thrombus excision. In another report Raghuram et al 6 used CPB with moderate hypothermia and low flow for removal of tumor thrombus. In our case we also used CPB with low flow and could achieve adequate clearance of the tumor thrombus without any complication.…”
Section: Case Reportmentioning
confidence: 99%
“…Noguchi K et al 5 reported the use of CPB in combination with hypothermic circulatory arrest (HCA) for complete tumor-thrombus excision. In another report Raghuram et al 6 used CPB with moderate hypothermia and low flow for removal of tumor thrombus. In our case we also used CPB with low flow and could achieve adequate clearance of the tumor thrombus without any complication.…”
Section: Case Reportmentioning
confidence: 99%